Keberadaan Model Partisipasi Anggota pada “Teras Tani” di Desa Karehkel, Bogor - Syaiful Syaiful; Arief Goeritno (Universitas Mathla'ul Anwar Banten, 2020)
EXISTENCES OF THE PARTICIPATION MODEL OF MEMBERS ON “TERAS TANI” IN DESA KAREHKEL, BOGOR. A preliminary study has been conducted to review the existence of the participation model of “Teras Tani” members in Desa Karehkel. Three descriptions are related to this, namely the inventory of activities of the members of “Teras Tani”, depiction of the basic conception of community participation according to Arnstein, and comparison of the reality of the participation of members of “Teras Tani” against the basic conception of participation according to Arnstein. Inventory of the activities of the members of the “Teras Tani”, including (i) implementing excellent programs, (ii) maintaining groupings in social interactions in the community, (iii) grouping rice fields, (iv) attention to the growth of superior rice plants, and (v) implementation harvest time. The depiction of the basic conception of community participation according to Arnstein, includes depictions of non-participation, tokenism, and the citizen power. Conclusions in accordance with the objectives of observing community service activities, namely (i) all members feel the benefits of the existence of farmer groups “Teras Tani”, (ii) typologies of steps of community participation can be easily illustrated in community organizations, one of them is a farmer group at the village level, and (iii) arguments for diverse citizen participation are emphasized on benefits through community organizing based on the same power.